Aerobic exercise with blood flow restriction affects mood state in a similar fashion to high intensity interval exercise - Gomes da Silva, J. C.; Fernandes Silva, K.; Domingos-Gomes, J. R.; Batista, G. R.; Domingos da Silva Freitas, E.; Cavalcanti Torres, V. B.; Cirilo-Sousa, M. S. (Physiology & Behavior, 2019)
We investigated the acute effects of aerobic exercise with blood flow restriction (BFR) on mood state in American football athletes. Twenty-two male American football athletes were randomly assigned to three experimental conditions: 1) aerobic exercise (AE: 40% VO2max), 2) aerobic exercise with BRF (AE + BFR: 40% VO2 max), and 3) high-intensity interval exercise (HIIE: 80% and 40% VO2max during exercise and the active intervals, respectively). Mood state and total mood disturbance (TMD) were assessed before, immediately post, and 1 h post-exerciser. Ratings of perceived exertion (RPE) were measured 30 min post-exercise. AE + BFR and HIIE significantly (p < 0.05) increased fatigue and tension compared to baseline immediately post-exercise, whereas vigor significantly (p < 0.05) decreased at the same time point for both conditions. TMD increased significantly (p < 0.05) for AE + BFR and HIIE immediately post-exercise and it remained elevated up to 1 h post-exercise for AE + BFR. AE did not significantly (p > 0.05) affect mood state or TMD and it was significantly (p < 0.05) lower than AE + BFR and HIIE. AE + BFR and HIIE also elicited significantly (p < 0.05) greater RPE levels than AE 30 min post-exercise. Therefore, AE + BFR induces acute impairments in mood state and RPE levels in a similar fashion to HIIE.